(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
In this article, the concept of "literacy" expands its content at the modern stage of development of pedagogical science.n this article, the concept of "literacy" expands its content at the modern stage of development of pedagogical science. If for a long time in science, the concept of "elementary literacy" in the quality of an indivi.